2021
DOI: 10.1111/bjh.17384
|View full text |Cite|
|
Sign up to set email alerts
|

The use of frailty assessments in treating older adults with aggressive lymphomas

Abstract: Summary Non‐Hodgkin lymphomas (NHL) are most commonly diagnosed among people aged 65–74 years, with a median age at diagnosis of 67 years. The percentage of NHL‐related deaths is highest among people aged 75–84 years, with a median age at death of 76 years from cases between 2014 and 2018. In light of these recent data, attending physicians of patients with NHL will recognize that the majority of their patients will be of advanced age, with many suffering from a spectrum of frailties. The excess rate of death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Our work adds to prior research by including a sample encompassing multiple age brackets across a broad set of aggressive NHL subtypes. Despite these promising survival outcomes in older adults, data suggest that older adults with lymphoma are often undertreated and that age alone is commonly used for treatment decision-making [9,10]. This is especially important in aggressive NHL, where intensive chemoimmunotherapy is potentially curative in a significant proportion of patients [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work adds to prior research by including a sample encompassing multiple age brackets across a broad set of aggressive NHL subtypes. Despite these promising survival outcomes in older adults, data suggest that older adults with lymphoma are often undertreated and that age alone is commonly used for treatment decision-making [9,10]. This is especially important in aggressive NHL, where intensive chemoimmunotherapy is potentially curative in a significant proportion of patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults often have multiple comorbid conditions, altered physical function and nutritional status, and impaired metabolism of chemotherapeutic agents [7,8]. However, older adults with lymphoma are often undertreated [9,10]. Importantly, the relative dose intensity to maximize survival for older patients with diffuse large B-cell lymphoma (DLBCL), the most common subtype of aggressive NHL, is unclear, as some studies have demonstrated an association between augmented relative dose intensity and prolonged survival, whereas others have shown similar survival with less intensive treatment approaches for frail patients [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The median age at the time of diagnosis is 66 years; furthermore, 20.1% of patients are diagnosed between 75 and 84 years of age, 25.0% between 65 and 74 years of age, and 21.2% between 55 and 64 years of age. At present, effective treatment among the elderly remains challenging owing to the adverse invasive biological characteristics of DLBCL, the baseline health status of this patient population, the late toxicity of chemotherapy, and the poor therapeutic effect of the current treatment scheme on elderly patients [8,9]. Therefore, interest in the understanding of the molecular and genetic pathways dysregulated in ageing and DLBCL has tremendously increased, along with the interest in biomarkers as a quick and quantitative measure in all areas of biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the optimal management of older individuals remains one of the greatest challenges in primary central nervous system lymphoma (PCNSL), as described for other diffuse large B‐cell lymphoma (DLBCL) subtypes 1,2 . Frailty, as a result of comorbidities, poor baseline performance status (PS) and other factors, as well as potential drug toxicity are considered major issues in treating patients within this age group 1,3–5 …”
mentioning
confidence: 99%
“…1,2 Frailty, as a result of comorbidities, poor baseline performance status (PS) and other factors, as well as potential drug toxicity are considered major issues in treating patients within this age group. 1,[3][4][5] An increasing incidence of PCNSL with age and more importantly, 6 extended life expectancy has resulted in increasing prevalence of PCNSL in an older population. 1,7 The median age of presentation of PCNSL has previously been reported at around 65 years although recently realworld data suggest it may be higher.…”
mentioning
confidence: 99%